Short-term effects of daily aspirin on cancer incidence, mortality, and non-vascular death: Analysis of the time course of risks and benefits in 51 randomised controlled trials - Rothwell, P; Price, J; Fowkes, F; Zanchetti, A; Roncaglioni, M; Tognoni, G; Lee, R; Belch, J; Wilson, M; Mehta, Z; Meade, T (2012)
Background Daily aspirin reduces the long-term risk of death due to cancer. However, the short-term effect is less certain, especially in women, effects on cancer incidence are largely unknown, and the time course of risk and benefit in primary prevention is unclear. We studied cancer deaths in all trials of daily aspirin versus control and the time course of effects of low-dose aspirin on cancer incidence and other outcomes in trials in primary prevention. Methods We studied individual patient data from randomised trials of daily aspirin versus no aspirin in prevention of vascular events. Death due to cancer, all non-vascular death, vascular death, and all deaths were assessed in all eligible trials. In trials of low-dose aspirin in primary prevention, we also established the time course of effects on incident cancer, major vascular events, and major extracranial bleeds, with stratifi cation by age, sex, and smoking status. Results Allocation to aspirin reduced cancer deaths (562 vs 664 deaths; odds ratio [OR] 0 85, 95% CI 0 76-0 96, p=0 008; 34 trials, 69 224 participants), par ticularly from 5 years onwards (92 vs 145; OR 0 63, 95% CI 0 49-0 82, p=0 0005), resulting in fewer non-vascular deaths overall (1021 vs 1173; OR 0 88, 95% CI 0 78-0 96, p=0 003; 51 trials, 77 549 participants). In trials in primary prevention, the reduction in non-vascular deaths accounted for 87 (91%) of 96 deaths prevented. In six trials of daily low-dose aspirin in primary prevention (35 535 participants), aspirin reduced cancer incidence from 3 years onwards (324 vs 421 cases; OR 0 76, 95% CI 0 66-0 88, p=0 0003) in women (132 vs 176; OR 0 75, 95% CI 0 59-0 94, p=0 01) and in men (192 vs 245; OR 0 77, 95% CI 0 63-0 93, p=0 008). The reduced risk of major vascular events on aspirin was initially off set by an increased risk of major bleeding, but effects on both outcomes diminished with increasing follow-up, leaving only the reduced risk of cancer (absolute reduction 3 13 [95% CI 1 44-4 82] per 1000 patients per year) from 3 years onwards. Case-fatality from major extracranial bleeds was also lower on aspirin than on control (8/203 vs 15/132; OR 0 32, 95% CI 0 12-0 83, p=0 009).